2015
DOI: 10.1016/j.otsr.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Cruciate-sacrificing total knee arthroplasty and insert design: A radiologic study of sagittal laxity

Abstract: IV - retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…Many studies have compared between TKAs with an UC insert and other design inserts. 9,[11][12][13][14]31,32 In terms of clinical outcomes, most of studies demonstrated similar results of UC design TKA with PS or CR, it is consistent with our study results. Multiple factors include geometry, implant size, type of insert, PCL integrity, and gap balancing are associated with AP instability in TKAs.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have compared between TKAs with an UC insert and other design inserts. 9,[11][12][13][14]31,32 In terms of clinical outcomes, most of studies demonstrated similar results of UC design TKA with PS or CR, it is consistent with our study results. Multiple factors include geometry, implant size, type of insert, PCL integrity, and gap balancing are associated with AP instability in TKAs.…”
Section: Discussionsupporting
confidence: 92%
“…This is to our knowledge the first study comparing intraoperative stability and ROM between fixed-bearing UC and PS TKA. The increased antero-posterior translation in the UC design is consistent with the findings of other studies in mobile-bearing TKA [1,10]. However, this seems to have no negative influence on PRO after short-term follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…Sagittal stability is an important consideration following TKA [5], but comparing stability in patients who underwent different types of TKA is difficult because it is influenced by several factors, including implant design geometry and surgical technique. The measurements of sagittal stability following UC TKA are conflicting in the literature [3, 4, 12, 13, 15, 16, 21]. Similar to the results of a study by Lützner et al [12], our results showed that AP stability following UC TKA at 90° of knee flexion was similar to that following CR TKA (7.5 mm in UC vs. 6.8 mm in CR knees).…”
Section: Discussionsupporting
confidence: 81%
“…Similar to the results of a study by Lützner et al [12], our results showed that AP stability following UC TKA at 90° of knee flexion was similar to that following CR TKA (7.5 mm in UC vs. 6.8 mm in CR knees). However, other studies have reported that UC TKA produced knees with more AP laxity than that following PS TKA [3, 17, 21].…”
Section: Discussionmentioning
confidence: 99%